2009
DOI: 10.3945/ajcn.2008.26668
|View full text |Cite
|
Sign up to set email alerts
|

Long-term leucine supplementation does not increase muscle mass or strength in healthy elderly men

Abstract: Long-term leucine supplementation (7.5 g/d) does not augment skeletal muscle mass or strength and does not improve glycemic control or the blood lipid profile in healthy elderly men. This trial was registered at clinicaltrials.gov as NCT00807508.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
218
3
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(251 citation statements)
references
References 38 publications
(58 reference statements)
14
218
3
16
Order By: Relevance
“…L‐Leu did not significantly stimulate protein synthesis and mTOR phosphorylation. These results are in agreement with those that demonstrate that supplementation with L‐Leu failed to elicit an additional response in rats12 or in well‐nourished healthy elderly men 37. Interestingly, our results showed that HMB was a significantly more active effector than L‐Leu under these conditions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…L‐Leu did not significantly stimulate protein synthesis and mTOR phosphorylation. These results are in agreement with those that demonstrate that supplementation with L‐Leu failed to elicit an additional response in rats12 or in well‐nourished healthy elderly men 37. Interestingly, our results showed that HMB was a significantly more active effector than L‐Leu under these conditions.…”
Section: Discussionsupporting
confidence: 93%
“…showed that while administration of low doses of L‐Leu‐stimulated protein synthesis in muscle in food‐deprived mature rats, further supplementation with L‐Leu failed to elicit an additional response. Verhoeven et al 37. also reported that long‐term supplementation of L‐Leu in well‐nourished healthy elderly men did not improve muscular mass and strength.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3,4 -5 g de Leucina) em conjunto com outras proteínas (ex: mix de proteínas) 9 ou na forma isolada 15 , e demonstraram aumento da TSP miofibrilar. Além disso, doses superiores a 4 g (ex: 7,5 g/dia) têm sido bem toleradas, em estudos em um longo prazo 16 .…”
Section: Suplementaçãounclassified
“…As a dietary supplement, leucine has been found to slow the degradation of muscle tissue by increasing the synthesis of muscle proteins in aged rats (Combaret et al, 2005). However, the supplementation of leucine with long-term didn't increase muscle mass or strength in healthy elderly men (Verhoeven et al, 2009). Until now, the dietary supplemental of leucine has not be associated the prime reason for muscular growth or optimal maintenance for the entire population.…”
Section: Compositions Of Essential Amino Acidsmentioning
confidence: 99%